What makes clinical labour different? The case of human guinea pigging - Różyńska, Joanna (Journal of medical ethics, 2018)
Each year thousands of individuals enrol in clinical trials as healthy volunteers to earn money. Some of them pursue research participation as a full-time or at least a part-time job. They call themselves professional or semiprofessional guinea pigs. The practice of paying healthy volunteers raises numerous ethical concerns. Different payment models have been discussed in literature. Dickert and Grady argue for a wage-payment model. This model gives research subjects a standardised hourly wage, and it is based on an assumption that research participation is morally indistinguishable from other forms of unskilled labour. In this paper, I will challenge this assumption. I will argue that human guinea pigging has particular characteristics which taken together make it significantly different from other forms of labour. (1) Participation in research is skill-independent. Healthy volunteers are valuable not because they are skilful persons, but because they are human bodies. (2) The role of research volunteers is mainly passive. They are not asked to produce goods or deliver services. They are paid for enduring unpleasant, painful and risky interventions performed by investigators. (3) Research volunteering involves inherent risks and uncertainties, and subjects have little or no control over their minimisation and materialisation. I conclude that participation in clinical research is a specific kind of activity. It is more like renting out one’s body to strangers, than working. Thus, research participation should not be treated on par with other forms of employment.